Uswag super strengthening urban revitalization through the redevelopment of the Iloilo Terminal Market - Carbon, Marc David L. (College of Architecture, University of the Philippines Diliman, 2020)
The City of Iloilo is one of the oldest cities in the Philippines. It harmoniously combines the past and the present despite its rapid transformation as a highly urbanized city and the regional center of Western Visayas. In 2008, the city government formulated a 20-year redevelopment plan for tor the revitalization of downtown Iloilo. This was an answer to the severe competition of local businesses against newer shopping malls. The plan was centered on two themes -- the improvement of both public infrastructure and private establishments as well as the conservation of heritage buildings. Yet despite the city's unprecedented economic growth and the government's conservation efforts, the city's public markets have yet to be redeveloped. To strengthen urban revitalization in the old downtown district, the project focuses on the redevelopment of the Iloilo Terminal Market (Super Market) -- the largest public market in the city and the bagsakan of local produce coming from nearby municipalities and provinces. Through methods of on-site observation, interviews, site analysis and other data gathering methods, the final project then becomes an example of a sustainable development that creates an impact in the built environment and the people living in it.